Comparing the Host Reaction to CorMatrix and Different Cardiac Patch Materials Implanted Subcutaneously in Growing Pigs - Mosala Nezhad, Zahra; Poncelet, Alain; Fervaille, Caroline; Gianello, Pierre (The Thoracic and Cardiovascular Surgeon, 2019)
Background Comparing the structural changes, and local host reactions to CorMatrix (CorMatrix Cardiovascular Inc., Roswell, Georgia, United States) and different biomaterials implanted subcutaneously in growing pig model.Methods Four pigs harboring implanted patches of CorMatrix, Vascutek porcine pericardium (Vascutek; Scotland, United Kingdom), SJM bovine pericardium (St. Jude Medical, Inc., Minnesota, United States), and Gore-Tex (W. L. Gore & Associates GmbH, Flagstaff, Arizona, United States) were studied for 1, 3, 6, and 12 months. The explants were examined histologically.Results CorMatrix showed gradual and consistent patch resorption and subsiding inflammatory and fibrosis process. Full scaffold degradation and replacement by mild fibrosis and subcutaneous tissue were seen by 1 year. Xenopericardial patches remained intact, and the initially severe inflammatory and fibrotic reactions reduced gradually to moderate fibrosis and chronic inflammation. Gore-Tex showed foreign body reaction.Conclusions Patches were biotolerated by pigs. Xenopericardial patches elicited encapsulating fibrosis and no remodeling. CorMatrix resorbs completely and degrades consistently without leaving residues. Lack of encapsulating fibrosis toward CorMatrix allows tissue ingrowth and matrix remodeling.
Keywords: CorMatrix; pericardium; experimental study